Food-insecure Canadians are more likely to visit emergency departments due to pain - Li, Tim (My University, 2023)
The researchers examined the relationship between household food insecurity and pain-driven emergency department visits by linking population survey data on food insecurity with emergency care records, which included number of emergency department visits because of pain, site of pain, and acuity (urgency) of visit.
Keywords: Health; Income, pensions, spending & wealth